Deletion of the waaf gene affects O antigen synthesis and pathogenicity in Vibrio parahaemolyticus from shellfish - Feng Zhao; Guoying Ding; Qilong Wang; Huihui Du; Guosheng Xiao; Deqing Zhou (Food Science and Human Wellness)
ibrio parahaemolyticus is the main cause of foodborne gastroenteritis, which is widely distributed in shellfish and other seafood. Most V. parahaemolyticus are nonpathogenic, and only a few types, such as serotype O3:K6, are pathogenic, which is also the most prevalent strain in Asia. However, the relationship between this serotype and pathogenicity has yet to be established. The waaf gene is located in the O antigen synthesis gene cluster. Thus, we constructed a waaf gene deletion mutant (i.e., △waaf) of wild-type (WT) which isolated from shellfish serotype O3:K6 via chitin-mediated transformation technology. We then constructed the △waaf complementary strain (i.e., C-Δwaaf) via the Escherichia coli S17 λpir strain by conjugation. The basic physiological characteristics, adhesion to Caco2 cells, and pathogenicity of the WT, Δwaaf, and C-Δwaaf strains were compared. Growth curves showed no remarkable differences between the WT and Δwaaf strains. However, the Δwaaf strain non-reactive to O3 antisera and other 12 O-group antisera of V. parahaemolyticus. Moreover, the number of flagella and extracellular polysaccharides decreased, the adhesion decreased, and the pathogenicity weakened. These characteristics of the C-Δwaaf strain were similar to those of the WT strain. These results indicated that the waaf gene is vital to the serotype in V. parahaemolyticus, and changes in O antigen could affect the pathogenicity of this bacterium. This study will be helpful to understand the pathogenic mechanism of V. parahaemolyticus.